Incidencia del trastorno por déficit de atención e hiperactividad en el rendimiento académico en los niños del grado primero de una institución educativa del Municipio de Maicao- La Guajira. (2023)
The general objective of this research is to “analyze the incidence of Attention Deficit Hyperactivity Disorder (ADHD) in the academic performance of children in the first grade of the Hernando José Hernández Sierra educational institution, located in the Municipality of Maicao, Department of La Guajira”. To do this, the theoretical foundation consisting of previous research and the theoretical and conceptual elements of the topic was developed. The method was established from the positivist paradigm with a quantitative approach, being a descriptive field research, with a correlational, non-experimental and transversal design. The study population is made up of 18 children in the 1st grade of the Hernando José Hernández Sierra educational institution, of which 6 have a diagnosis of ADHD; For the sample, a census-type deterministic approach was chosen.